Rheological characterisation and modelling of bitumen containing reclaimed components. Issue Volume 20:Issued 6(2019) (3rd June 2019) - Blasl, Anita; Khalili, Mohamadreza; Canon Falla, Gustavo; Oeser, Markus; Liu, Pengfei; Wellner, Frohmut
ABSTRACT: Currently, many efforts are undertaken to reach asphalt performance from binder performance in order to reduce costly and time consuming laboratory tests on asphalt materials. In this context, it is important to use and develop appropriate testing methods for a comprehensive binder characterisation, which requires suitable material models. Depending on the application, different models can be used to model rheological bitumen behaviour. This paper focuses on the applicability of the Christensen and Anderson model (CA model) and the Olard-Di Benedetto (2S2P1D) model for bitumen samples containing different amounts of recycled components using various objective functions in the optimisation process. The purpose is to analyse the influence of the reclaimed asphalt rate on the parameters of the investigated models. Dynamic Shear Rheometer tests are conducted on binder samples extracted from Stone Mastic Asphalt mixes with polymer modified bitumen and Asphalt Concrete mixes with paving bitumen, each containing 0–100% reclaimed material components. The resulting influences of the recycled materials are illustrated through master curves, black diagrams and Cole–Cole plots by fitting these experimental data by the application of 2S2P1D and CA model.